The Prevalence of Cosmetic Facial Plastic Procedures among Facial Plastic Surgeons - Moayer, Roxana; Sand, Jordan P.; Han, Albert; Nabili, Vishad; Keller, Gregory S. (Facial Plastic Surgery, 2018)
This is the first study to report on the prevalence of cosmetic facial plastic surgery use among facial plastic surgeons. The aim of this study is to determine the frequency with which facial plastic surgeons have cosmetic procedures themselves. A secondary aim is to determine whether trends in usage of cosmetic facial procedures among facial plastic surgeons are similar to that of nonsurgeons. The study design was an anonymous, five-question, Internet survey distributed via email set in a single academic institution. Board-certified members of the American Academy of Facial Plastic and Reconstructive Surgery (AAFPRS) were included in this study. Self-reported history of cosmetic facial plastic surgery or minimally invasive procedures were recorded. The survey also queried participants for demographic data. A total of 216 members of the AAFPRS responded to the questionnaire. Ninety percent of respondents were male (n = 192) and 10.3% were female (n = 22). Thirty-three percent of respondents were aged 31 to 40 years (n = 70), 25% were aged 41 to 50 years (n = 53), 21.4% were aged 51 to 60 years (n = 46), and 20.5% were older than 60 years (n = 44). Thirty-six percent of respondents had a surgical cosmetic facial procedure and 75% has at least one minimally invasive cosmetic facial procedure. Facial plastic surgeons are frequent users of cosmetic facial plastic surgery. This finding may be due to access, knowledge base, values, or attitudes. By better understanding surgeon attitudes toward facial plastic surgery, we can improve communication with patients and delivery of care. This study is a first step in understanding use of facial plastic procedures among facial plastic surgeons.
Keywords: surgeons; cosmetic; prevalence; minimally invasive; facial plastic surgery